Dialogue with surroundings - Nowicka, Aleksandra (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The article raises a subject of context in architecture, its influence on shape, perception and evaluation of existing and erecting buildings. In the text the attention is paid to diverse forms of context (referring to space, historical conditions, construction and materials, tradition) and their meaning in the architecture design. In the light of today spatial actions and planning it is turning out that it is important to respect context as a one of the most relevant criteria of creating valuable and honest architecture, which suits to its users needs and which remains in interesting relations with its surroundings.